Rekomendācijas un metodes kreiļu prasmju pilnveidē 1. klases 1. semestrī - Pudža-Nemkoviča, Ieva (Latvijas Universitāte, 2008)
Darba autore: Ieva Pudža - Nemkoviča diplomdarbā ”Rekomendācijas un metodes kreiļu prasmju pilnveidē 1. klasēm 1.semestrī”, analizē kreilības problēmas un izstrādāti ieteikumus vecākiem un skolotājiem, lai novērstu mācību grūtības skolēniem- kreiļiem. Kreilības jautājums ir bijis ļoti aktuāls un būs vienmēr, jo viss ir piemērots labročiem ne tikai saistībā ar skolu, bet arī ikdienas dzīvē. Kreiļa turpmākā dzīve ir atkarīga sākumposmā galvenokārt no vecākiem, no tā kā viņi skatās uz to, ka viņu bērns ir kreilis, vai viņi rūpējas par viņa vajadzībām un seko līdzi viņa attīstībai un mācībām skolā. Skola ir vieta, kurā parūpējas, lai bērns iemācītos sev nepieciešamās lietas, attīstītu savas fiziskās un garīgās prasmes un tiktu sagatavots turpmākajai dzīvei, tāpēc ir ļoti svarīgi sākumposmā bērnam-kreilim palīdzēt iekļauties skolas dzīvē un mazināt tās īpašības, kas izraisa nedrošību, biklumu un kautrīgumu. Atslēgvārdi: prasmes, kreilība, kreilības riska faktori, rekomendācijas.

Author: Ieva Pudža – Nemkoviča. The title of Diploma Paper: Recommendations and Methods in Improvement of Skills for Left – handed Students in Form 1. The Diploma Paper has been worked out in pedagogy. Problem of left – handed students as well as advises for parents and teachers have been worked out to avert difficulties in the process of learning. The paper consists of: introduction, annotations in Latvian and English, 4 chapters, the research part, conclusions and the list of used literature. The aim of research: to analyze problems connected with left – handed students and work out advices for parents and teachers to avert problems in learning process. Research methods: analyses of literature, questioning, interviewing, observation and summary of the results. The problem for the left – handed has always been urgent and such it will be because everything is meant for right – handed people not only at school but also in everyday life. The future life of a left – handed student depends on how parents accept, support and understand their child’s needs and help him with his studies at school. School is a place where care is taken of such children. They are taught how to develop their physical and mental skills, they are prepared for their future life. It is very important to help the left – handed students in their first year at school and support them in order to lessen such traits as unsafely and shyness. Keywords: skill, lefty, lefty risk factors, recommendatory.
Recommendations and methods for improving the skills of left-handers in the first term in Grade 1
Keywords: Pedagoģija